2011
DOI: 10.1002/chin.201134126
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Ketenimine N‐Functionalization of Thiazolidine‐3,4‐diones with Acetylenes and Isocyanides.

Abstract: Ketenimine N-Functionalization of Thiazolidine-3,4-diones with Acetylenes and Isocyanides. -The three-component one-pot reaction of thiazolidinediones with alkyl isocyanides and dialkyl acetylenedicarboxylates gives highly functionalized stable ketenimines. A plausible mechanism is provided. -(YAVARI*, I.; SANAEISHOAR, T.; AZAD, L.; GHAZVINI, M.; Mendeleev Commun. 21 (2011) 2, 108-109, http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The preferred substitutions included; R ¼ OEt, R 0 ¼ n-Bu and R 00 ¼ 4-Br-C 6 H 4 , COOEt, 4-MeO-C 6 H 4 . 26 Another reaction of 1-aryl-1H-pyrrole-2,5-diones 24 with nonstabilized azomethineylides, which were generated in situ via decarboxylative condensation of isatins 25 and sarcosine 26, afforded only one product i.e. 4 0 -aryl-5 0 a,6 0 -dihydro-1 0 -Scheme 3 Synthesis of 2-aminopyrrole scaffold.…”
Section: Synthetic Routes Of Pyrrole and Its Analogsmentioning
confidence: 99%
“…The preferred substitutions included; R ¼ OEt, R 0 ¼ n-Bu and R 00 ¼ 4-Br-C 6 H 4 , COOEt, 4-MeO-C 6 H 4 . 26 Another reaction of 1-aryl-1H-pyrrole-2,5-diones 24 with nonstabilized azomethineylides, which were generated in situ via decarboxylative condensation of isatins 25 and sarcosine 26, afforded only one product i.e. 4 0 -aryl-5 0 a,6 0 -dihydro-1 0 -Scheme 3 Synthesis of 2-aminopyrrole scaffold.…”
Section: Synthetic Routes Of Pyrrole and Its Analogsmentioning
confidence: 99%
“…NMR spectra were recorded with a Bruker DRX-300 Avance instrument (300 MHz for 1 H and 75.4 MHz for 13 C) with acetone-d 6 General procedure for the synthesis of compounds 5 and 6. NMR spectra were recorded with a Bruker DRX-300 Avance instrument (300 MHz for 1 H and 75.4 MHz for 13 C) with acetone-d 6 General procedure for the synthesis of compounds 5 and 6.…”
Section: Methodsmentioning
confidence: 99%
“…13 It has been shown that these types of zwitterions can be trapped by a variety of organic acids. [14][15][16][17] In continuation of current interest in the development of new routes to heterocyclic and carbocyclic systems, [18][19][20][21][22][23][24][25][26] we became interested in developing novel and efficient methods to construct the new 1,2-dihydroisoquinoline-based structures, with a hope of finding active hits for our particular biological assays. Herein, we report a synthesis of 1,2-dihydroisoquinolines via the three-component reaction of isoquinoline, alkyl propiolates, and CH-acids, under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%